Hubungan Self Efficacy terhadap Penggunaan Chatbot AI dalam Pengerjaan Tugas Mahasiswa Semester 7 Tadris Matematika UIN Raden Mas Said Tahun Ajaran 2025/2026 - Toha, Andi Muhammad; Astuti, Wiwin (Universitas PGRI Semarang, 2026)
This study aims to examine the relationship between self-efficacy and the use of AI chatbots in completing academic assignments among Mathematics Education students. A quantitative approach with a correlational design was employed. The research population consisted of 81 students from three classes, and the sample was selected using cluster random sampling by taking two classes. Data were collected through self-efficacy and AI chatbot usage questionnaires that had met validity and reliability requirements. Data analysis included descriptive statistics, prerequisite tests, Pearson correlation analysis, and simple linear regression. The results revealed a positive and significant relationship between self-efficacy and AI chatbot usage, with a correlation coefficient of r = 0.422 and a significance value of 0.001. Regression analysis indicated that self-efficacy contributed 17.8% to the use of AI chatbots. These findings suggest that students with higher self-efficacy tend to utilize AI chatbots more adaptively as supportive learning tools. Therefore, strengthening students’ self-efficacy is essential to ensure that AI chatbot usage effectively supports mathematics learning.